Study on the biodegradation of phenol by Alcaligenes faecalis JH1 immobilized in rice husk biochar - Li, Manzhi; Xiao, Jiahui; Zeng, Zhi; Zhang, Taiping; Ren, Yuan (Frontiers in Environmental Science, 2023)
Immobilized microbial technology is a sustainable solution to reduce water pollution. Understanding the microorganisms in immobilized biochar is critical for the removal of contaminants in water. Biochar as a carrier of microorganisms, there are some problems need to be focused on, microporous structure blockage limiting the contact between microorganisms and pollutants for further degradation, unstable microbial loading, and low cycle times. To solve these problems, Alcaligenes faecalis was immobilized with rice hull biochar to study its adsorption and degradation characteristics of phenol. It was found that Alcaligenes faecalis JH1 could effectively remove 300 mg/L of phenol within 24 h. The adsorption capacity of rice husk biochar for phenol increased with the increasing pyrolysis temperature (700>500>300 o C). The immobilized biomass of JH1 from 700 o C rice husk biochar reached 249.45 nmol P/g at 24 h of fixation reaction. It was found that the phenol removal rate of JH1 immobilized at all temperature biochar reached 300 mg/L within 12 h after the sixth cycle. As the number of cycles increased, bacteria grew and adhered to the biochar, forming a thick viscous biofilm and accelerating the removal of phenol. The results showed that Alcaligenes faecalis could firmly adhere to rice hull biochar and degrade phenol effectively, with good durability and cyclicity.